(untitled) (Herald of Journalism, 2018)
The article considers the activities of the Assembly of the people of Kazakhstan and stresses the importance of forming public opinion on this issue in the media. The author believes that the activity of the Assembly is one of the most important social and political structures of society, which represents a new stage and information about it must be increased in the mass media.